Prostate cancer: relationship with depression and suicidal thoughts - A. A. Keln; D. G. Alifov; S. A. Zvezda; M. A. Zasorina (Вестник урологии, 2022)
Prostate cancer is one of the most common malignancies among men, accounting for 19% of malignant neoplasms and the third leading cause of cancer-related death. The suicide rate among men around the world has increased over the past decade. Additionally, suicide rates are higher among cancer patients, including those with prostate cancer, compared to the general population. The article aimed to make review the current literature and determine the correlation between prostate cancer, depression, and suicidal thoughts.